The Effect of Capital Expenditure and Balancing Funds on Regional Financial Performance Through Regional Original Revenue - Philep Njonjie; Agustin Bagu (STIE Tri Bhakti, 2025)
This study was conducted to examine the effect of capital expenditure and balancing funds on regional financial performance, with regional revenue as a mediating variable. The objects of this study were 12 regencies and 3 cities in the provinces of Maluku and North Maluku. This study was quantitative in nature. The sample was determined using the census method. The data used are secondary data sourced from the Budget Realization Report (LRA) of the Supreme Audit Agency (BPK) of the Republic of Indonesia, website www.bpk.go.id, from 2020 to 2023. The data were tested using Partial Least Square testing with a significance level of 5% and using WarpPLS 8.0 software. The results of the study indicate that capital expenditure and balancing funds have a significant positive effect on local revenue, local revenue and capital expenditure have a significant positive effect on local financial performance, while balancing funds do not have a significant effect on local financial performance. Local revenue mediates the relationship between capital expenditure and local financial performance, as well as between balancing funds and local financial performance. Keywords: Capital Expenditure, Fiscal Equalization Funds, Local Government Revenue, Local Government Financial Performance